Quality human resource management in higher education - Noor Azman Ali (Penerbit Universiti Putra Malaysia, 2009)
This book covers information on people or soft aspects of quality management perspectives. This includes discussions on critical HRM factors that would ensure success in the implementation of quality management. The higher education cases based on primary research are brought into the perspective to strengthen the theoretical foundation of the related concepts. Organizational performance measures that is pertinent to indicate the effectiveness of quality initiatives is also discussed and supported with extensive references.